Invention and utilization of epoch of Kifilideen sum formula for Kifilideen general matrix progression series of infinite terms in solving word problems: Epoch of Kifilideen’s sum formula for Kifilideen’s general matrix progression series of infinite terms in solving real-world problems - Osanyinpeju, Kifilideen (Journal of Innovative Applied Mathematics and Computational Sciences, 2024)
Kifilideen’s general matrix progression series of infinite terms is the summation of values of a collection of progressive members of the numbers series system. The number series system or set has endless terms where terms are progressive into levels and steps (within level) with increasing members set in successive levels and just one member in the first level. This kind of series is needed in determining the overall value(s) of the collection in the progressive members of the system which is/are useful for budgeting, analyzing, accounting, allocating and planning the system of arrangement that adopts such series. This study invented and applied the epoch of Kifilideen’s Sum Formula for Kifilideen’s General Matrix Progression Series of infinite terms in solving real-world problems. The mathematical induction of sum formulas of bi–numbers product progression series was formulated and established. These sum formulas obtained were incorporated into inventing Kifilideen’s Sum Formula for Kifilideen’s General Matrix Progression Series of infinite terms. The Kifilideen’s Sum Formula invented in this paper and Kifilideen’s Components Formulas of the Kifilideen’s general matrix progression sequence of infinite terms were used in conjunction to proffer solutions to real-world problems. The established Kifilideen’s Sum Formula for Kifilideen’s General Matrix Progression Series of infinite terms provides an easy and fastening process of finding the summation and evaluation of the overall value(s) of collection of progressive members of the Kifilideen’s General Matrix Progression Series of infinite terms.